2014
DOI: 10.1186/1752-0509-8-s2-s4
|View full text |Cite
|
Sign up to set email alerts
|

Integrative omics analysis. A study based on Plasmodium falciparum mRNA and protein data

Abstract: BackgroundTechnological improvements have shifted the focus from data generation to data analysis. The availability of large amounts of data from transcriptomics, protemics and metabolomics experiments raise new questions concerning suitable integrative analysis methods. We compare three integrative analysis techniques (co-inertia analysis, generalized singular value decomposition and integrative biclustering) by applying them to gene and protein abundance data from the six life cycle stages of Plasmodium falc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…Multiple Coinertia Analysis (MCIA)-MCIA is an integrative analysis method that can be applied to multiple (OMICS) data sets simultaneously (16,17). The data sets are matrices in which the number of features, typically stored in the rows, is much larger than the number of samples, typically stored in the columns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple Coinertia Analysis (MCIA)-MCIA is an integrative analysis method that can be applied to multiple (OMICS) data sets simultaneously (16,17). The data sets are matrices in which the number of features, typically stored in the rows, is much larger than the number of samples, typically stored in the columns.…”
Section: Methodsmentioning
confidence: 99%
“…Comparisons Between Phagocyte Proteome Profiles and Published Hemocyte Transcriptomes-To compare our granulocyte-enriched proteomes (SF, BF, PF) (supplemental Table S4) with existing hemocyte transcriptional profiles (8), we performed MCIA (16,17) to determine the correlation between protein and transcript data. Granulocyte protein samples were directly compared with transcriptional profiles produced by Pinto et al (8) of nonselected hemocytes from naïve sugar-fed mosquitoes, 24 h after feeding with a noninvasive CTRP mutant Plasmodium berghei (comparable to a noninfectious blood meal), or 24 h post-infection with wild-type P. berghei (8).…”
Section: Identification Of Candidate Proteins Enriched In Response Tomentioning
confidence: 99%
“…This demonstrated that the GSVD can be used to correctly predict previously unknown cellular mechanisms. Since then, the GSVD has been used to separate the similar from the dissimilar between different species, as well as between different types of molecular biological profiles, mostly large-scale (e.g., mRNA and protein expression in addition to DNA copy-number profiles), and different profiling technologies (e.g., NGS and quantitative real-time PCR in addition to DNA microarray platforms) [1823] (see also [24–26]).…”
Section: Discussionmentioning
confidence: 99%
“…Rezola et al 2014;Tomescu et al 2014). Notwithstanding the expense and complex bioinformatics challenges associated with such integration, its uptake is likely to increase in future.…”
Section: Molecular and Biochemical Tricks Of The Aquaculture Researchmentioning
confidence: 97%